2017
DOI: 10.1007/s00590-017-2042-5
|View full text |Cite
|
Sign up to set email alerts
|

Low incidence of postoperative urinary retention with the use of a nurse-led bladder scan protocol after hip and knee arthroplasty: a retrospective cohort study

Abstract: A retrospective cohort study, Level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 27 publications
0
28
0
Order By: Relevance
“…The main features and results of the 15 studies are presented in Table 1. 2,[10][11][12][13][14][15][16][17][18][19][20][21][22][23] Diagnostic criteria and incidence of POUR In all of the 15 studies, the diagnosis of POUR was made by ultrasound. Each study adopted various volume criteria from 350 mL to 700 mL for the diagnosis of POUR.…”
Section: Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The main features and results of the 15 studies are presented in Table 1. 2,[10][11][12][13][14][15][16][17][18][19][20][21][22][23] Diagnostic criteria and incidence of POUR In all of the 15 studies, the diagnosis of POUR was made by ultrasound. Each study adopted various volume criteria from 350 mL to 700 mL for the diagnosis of POUR.…”
Section: Search Resultsmentioning
confidence: 99%
“…Recent studies reported that monitoring with the use of an ultrasound scan decreases the incidence of POUR and recommended the ultrasound scan at 6–8 h after the start of anesthesia. 15,19,25 In all studies, POUR patients were treated with intermittent catheterization. In case of inevitable use of an indwelling catheter, it should be removed within 48 h, because the duration of catheterization is closely related with the development of UTI.…”
Section: Discussionmentioning
confidence: 99%
“…For patients, increased adherence to guidelines for voiding care in the orthopaedic context can decrease the risk of adverse events and complications associated with hip surgery [ 52 ], particularly the often preventable risk of urinary retention [ 53 ]. Further, advanced interprofessional teamwork to address urinary retention is likely to incorporate the patient perspective, enhancing opportunities for individuals to participate in issues regarding their health and healthcare [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…With the development of fast-track protocols after TJAs, it is imperative that POUR can be quickly identified and managed to reduce the development of subsequent complications. Previous studies have used routine postoperative bladder scans, stating that bladder volumes of greater than 200 mL significantly increases the risk of developing POUR [9]. On review of the literature, the risk factors associated with the development of POUR after prophylactic indwelling catheterization have been sparingly defined and their consequential effect on renal function has been understudied.…”
Section: Introductionmentioning
confidence: 99%